ANALISIS PENGGUNAAN MEDIA KARTU KATA PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS II SDN PAKUJAYA 01 KOTA TANGERANG SELATAN - Nur Maulida, Luthfia; Nurfadhillah, Septy; Nuraeni, Yeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was motivated by the results of initial observations which showed that the use of word card media in Indonesian language learning in class II at SDN Pakujaya 01, South Tangerang City was still not optimal. Teachers do not fully understand the potential and benefits of this media, so students feel bored and less active in the learning process. This has an impact on students' low understanding and mastery of vocabulary as well as difficulties in making sentences from certain vocabulary. The aim of this research is to determine the use of word card media in Indonesian language learning in class II at SDN Pakujaya 01, South Tangerang City. The method used is qualitative.. Data collection techniques use observation, interviews and documentation. The research results show that word card media is very effective in increasing students' understanding of vocabulary and lesson material. Word cards that are adapted to the learning theme and curriculum have succeeded in creating an active and participatory learning atmosphere. Students show high enthusiasm and involvement in vocabulary reading and group activities. The Cooperative Learning method applied by teachers has also proven effective in strengthening students' understanding and supporting the development of interpersonal and collaborative skills. Thus, word card media not only functions as a learning aid, but also as a medium that supports social interaction and student learning motivation. Keywords: elementary education, indonesian language learning, word cards